The Role of Innovation as the Key to Successful Muslim Women Entrepreneurs - Laily, Nur; Triyonowati, Triyonowati; Suwitho, Suwitho; Ernawati, Dyah Poespita (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
Muslim women can run their businesses to support the family economy and the country's economy. This study aims to determine the effect of Knowledge Sharing and Social Capital on Innovation and Business Performance. The population in this study is Muslim women as owners of SMEs in Indonesia. Three hundred seventeen respondents were selected using specific criteria. The data was obtained by using a questionnaire—data analysis using PLS-SEM. The results showed that Knowledge Sharing and Social Capital affected Innovation and Business Performance. Besides that, innovation can be a mediator of Knowledge Sharing and Social Capital influencing business.